EDUKASI PENERAPAN SISTEM INFORMASI MANAJEMEN PUSKESMAS (SIMPUS) DALAM PELAYANAN PUBLIK DI PUSKESMAS DELI TUA - Sembiring, Ripando; Malau, Pitto Pratiwi; Surbakti, Desmayanti; Sembiring, Mega Claudia (Jurnal Pengabdian Masyarakat Putri Hijau, 2023)
The research objective of the Implementation of the Community Health Center Management Information System (Simpus) on Patient Satisfaction at the Deli Tua Community Health Center in 2023 is to analyze the influence of health service quality on outpatient patient satisfaction. In the Deli Tua Community Health Center working area, JKN participants use quantitative observation and cross-sectional analytical methods, investigating how and why this phenomenon occurs. Then analyze the dynamics of the correlation of phenomena or risk factors and influence factors from the results of the research carried out. Analysis of the relationship between the implementation of the Community Health Center Management Information System (Simpus) and patient satisfaction with p-value (0.002); compared to 0.05, it can be concluded that Ha is accepted with Ho, which means there is a relationship between the implementation of the Puskesmas management information system and the patient satisfaction of the Deli Tua Health Center, and the decision to study the implementation of the Puskesmas Management Information System (Simpus) has an effect on the patient satisfaction of the Deli Tua Health Center. conclusion on the implementation of information at the Deli Tua Health Center.